Insights from UKCTOCS for design, conduct and analyses of large randomised controlled trials - Usha Menon; Aleksandra Gentry-Maharaj; Matthew Burnell; Sophia Apostolidou; Andy Ryan; Jatinderpal K Kalsi; Naveena Singh; Lesley Fallowfield; Alistair J McGuire; Stuart Campbell; Steven J Skates; Anne Dawnay; et al. (Health Technology Assessment)
Randomised controlled trials are challenging to deliver. There is a constant need to review and refine recruitment and implementation strategies if they are to be completed on time and within budget. We present the strategies adopted in the United Kingdom Collaborative Trial of Ovarian Cancer Screening, one of the largest individually randomised controlled trials in the world. The trial recruited over 202,000 women (2001–5) and delivered over 670,000 annual screens (2001–11) and over 3 million women-years of follow-up (2001–20). Key to the successful completion were the involvement of senior investigators in the day-to-day running of the trial, proactive trial management and willingness to innovate and use technology. Our underlying ethos was that trial participants should always be at the centre of all our processes. We ensured that they were able to contact either the site or the coordinating centre teams for clarifications about their results, for follow-up and for rescheduling of appointments. To facilitate this, we shared personal identifiers (with consent) with both teams and had dedicated reception staff at both site and coordinating centre. Key aspects were a comprehensive online trial management system which included an electronic data capture system (resulting in an almost paperless trial), biobanking, monitoring and project management modules. The automation of algorithms (to ascertain eligibility and classify results and ensuing actions) and processes (scheduling of appointments, printing of letters, etc.) ensured the protocol was closely followed and timelines were met. Significant engagement with participants ensured retention and low rates of complaints. Our solutions to the design, conduct and analyses issues we faced are highly relevant, given the renewed focus on trials for early detection of cancer. Future work There is a pressing need to increase the evidence base to support decision making about all aspects of trial methodology. Trial registration ISRCTN-22488978; ClinicalTrials.gov-NCT00058032. Funding This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme as award number 16/46/01. The long-term follow-up UKCTOCS (2015 20) was supported by National Institute for Health and Care Research (NIHR HTA grant 16/46/01), Cancer Research UK, and The Eve Appeal. UKCTOCS (2001–14) was funded by the MRC (G9901012 and G0801228), Cancer Research UK (C1479/A2884), and the UK Department of Health, with additional support from The Eve Appeal. Researchers at UCL were supported by the NIHR UCL Hospitals Biomedical Research Centre and by the MRC Clinical Trials Unit at UCL core funding (MC_UU_00004/09, MC_UU_00004/08, MC_UU_00004/07). The views expressed are those of the authors and not necessarily those of the NHS, the NIHR, or the UK Department of Health and Social Care. Plain language summary Randomised controlled trials help us decide whether new health-care approaches are better than those in current use. To successfully complete these on time and within budget, there is a constant need to review and revise the procedures used for delivering various aspects such as invitation, enrolment, follow-up of participants, delivery of the new test, data collection, and analysis. We report on the processes used in the United Kingdom Collaborative Trial of Ovarian Cancer Screening, one of the largest such trials. The United Kingdom Collaborative Trial of Ovarian Cancer Screening enrolled over 202,000 women (2001–5), delivered over 670,000 yearly screens (2001–11) and followed all participants until 2020. Key to our successful completion were the involvement of senior investigators in day-to-day running of the trial, a pre-emptive approach to issues, a willingness to innovate, and the use of technology. Our underlying ethos was that trial participants should always be at the centre of all our processes. We ensured that they were able to always contact either their local or the central team for clarifications and rescheduling of appointments. To facilitate this, we shared participant contact details (with consent) with both teams. We built a comprehensive electronic system to manage all aspects of the trial. This included online forms that the teams completed in real time (resulting in an almost paperless trial) and systems to check and manage trial processes and track blood samples. We automated key steps such as checking whether participants were eligible, assigning correct action based on results of screening tests, scheduling appointments and printing letters. As a result, all participants were treated as set out in the trial plan. Our engagement with participants ensured that they continued participating and we had a low rate of complaints. We faced issues with regard to our initial trial design and the way we planned to analyse the data. We feel that our solutions are highly relevant, especially as there is a renewed focus on trials for early detection of cancer.